Acceptability of Routine Point-of-Care Early Infant Diagnosis in Eight African Countries: Findings From a Qualitative Assessment of Clinical and Laboratory Personnel. (1st July 2020) - Bianchi, Flavia; Clemens, Sara; Arif, Zainab; Sacks, Emma; Cohn, Jennifer
Abstract : Background: The Elizabeth Glaser Pediatric AIDS Foundation introduced point-of-care (POC) testing for early infant diagnosis (EID) of HIV in 8 African countries. Understanding experiences and opinions of users can help facilitate introduction and sustainability. Setting: Cameroon, Côte d'Ivoire, Eswatini, Kenya, Lesotho, Mozambique, Rwanda, and Zimbabwe. Methods: Structured interviews with health care workers (HCWs) providing EID services and semistructured interviews with national and regional laboratory managers or EID program managers were conducted before and after the implementation of POC EID. Survey responses were analyzed and compared; open-ended responses were analyzed by theme. Results: In total, 234 and 175 interviews with HCWs and 28 and 14 interviews with laboratory or program managers were conducted before and after the introduction of POC EID, respectively. In preintervention interviews, challenges identified with laboratory-based EID testing included distance from patients' residence to the health facility, time-consuming sample transportation to central laboratories, stockout of testing kits, and long wait times for results. Postintervention data revealed that HCWs found POC EID easy to use and were very satisfied with the fast turnaround time and ability to initiate treatment for HIV-infected infants sooner. Laboratory managers were also supportive of scaling-up POC testing although cautious of the need for reliable infrastructure to operate platforms. The recommendation was that POC EID be integrated within the national diagnostic testing network. Conclusions: Support for POC EID from key stakeholders is essential for sustainability. Overall, participants supported the rollout of POC testing for EID, noting challenges and opportunities for scaling-up POC EID and recommending integration into the overall EID system.